2018
DOI: 10.1002/term.2747
|View full text |Cite
|
Sign up to set email alerts
|

Endothelialization mechanisms in vascular grafts

Abstract: Despite the wide variety of tissue-engineered vascular grafts that are currently being developed, autologous vessels, such as the saphenous vein, are still the gold standard grafts for surgical treatment of vascular disease. Recently developed technologies have shown promising results in preclinical studies, but they still do not overcome the issues that native vessels present, and only a few have made the transition into clinical use. The endothelial lining is a key aspect for the success or failure of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 98 publications
(346 reference statements)
0
101
0
Order By: Relevance
“…The use of autografts, like the saphenous vein or mammary artery, are still the standard clinical approach for the replacement of small diameter blood vessels [3]. However, mechanical or size mismatches, and mainly the scarce availability make alternative grafts necessary [4,5]. In this context, two strategies have emerged in recent years: synthetic substitutes and biological grafts [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of autografts, like the saphenous vein or mammary artery, are still the standard clinical approach for the replacement of small diameter blood vessels [3]. However, mechanical or size mismatches, and mainly the scarce availability make alternative grafts necessary [4,5]. In this context, two strategies have emerged in recent years: synthetic substitutes and biological grafts [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical or size mismatches, and mainly the scarce availability make alternative grafts necessary [4,5]. In this context, two strategies have emerged in recent years: synthetic substitutes and biological grafts [4]. Although large-diameter synthetic substitutes (>6 mm) are successfully used, small diameter grafts (<6 mm) show low patency rates due to their tendency to elicit thrombosis and the formation of intimal hyperplasia [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Easing the vascular wall repopulation and biomechanical adaptation was needed for further development of ex vivo scaffolds as vascular grafts. Additional development of an endothelial layer to avoid thrombosis of the vessel upon implantation is also crucial (Sánchez, Brey, & Briceño, 2018). It has previously been demonstrated that the re-endothelialization of the acellular human umbilical vein can similarly be performed using sequential conditioning steps (Uzarski, Cores, & McFetridge, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…45 In vivo, there are three known spontaneous modes of endothelialization: transanastomotic ingrowth, transmural capillarization, and fallout endothelialization. 46 For an extensive review on the different endothelialization mechanisms in vascular grafts, see Sánchez et al 46 Transanastomotic endothelialization consists in the growth of the host intimal layer from the anastomosis site towards the middle of the graft: native ECs migrate through the anastomosis region. 47 However, if this mechanism of endothelialization is well known and allows to fully endothelialize the short-to middle-sized grafts in animal models, it does not take place that well in human beings.…”
Section: Vascular Tissue Engineering and The Endotheliummentioning
confidence: 99%